Modelling, optimisation and evaluation of multi-transmitters FSO link for ground to train communication - A. Alhartomi, Mohammed; Abdullah, M.F.L.; Mabrouk, Wafi A.B.; Alzahmi, Ahmed; Alzahrani, Saeed (elsevier, 2025)
This paper investigates the potential of Free Space Optical (FSO) communication technology for high-speed train (HST) systems by developing mathematical models for G2T-FSO (Ground to Train) communication links across single, curved, and double-curved tracks. The key contribution of this research is the introduction of novel G2TFSO models, incorporating multiple transmitters (single, double, triple, and quad) and considering different weather conditions (clear, rain, and fog) using NRZ-OOK modulation. The models were evaluated based on key performance metrics, including received power, signal-to-noise ratio (SNR), bit error rate (BER), and eye diagrams. Simulation results reveal that single and dual transmitter links are significantly impacted by geometrical and atmospheric losses, while triple and quad transmitters provide error-free G2T-FSO links with a BER of 10-9. Under clear weather conditions, communication ranges of up to 680 meters for straight tracks and 618 meters for curved tracks were achieved. These findings highlight that G2T-FSO links deliver superior performance compared to traditional HST communication technologies, offering enhanced range, reliability, and data capacity for high-speed, secure train communication systems.